On the correlation between fracture toughness and crash resistance of advanced high strength steels. (January 2019) - Frómeta, D.; Lara, A.; Molas, S.; Casellas, D.; Rehrl, J.; Suppan, C.; Larour, P.; Calvo, J.
Highlights: A fracture mechanics approach to assess the impact performance of AHSS is presented. Fracture resistance is evaluated through the essential work of fracture methodology. Toughness is measured in terms of crack initiation and propagation resistance. Crash resistance of AHSS is described according to a cracking pattern in crash tests. Steels with higher essential work of fracture, we, present better crash performance. Abstract: Automotive industry players have devoted large efforts to identify the material parameters governing the crash resistance of Advanced High Strength Steels (AHSS). Such knowledge is essential to improve impact performance prediction and optimize new steel development. Nevertheless, there is still an open discussion about which are the most relevant properties on AHSS crashworthiness. In this work, the authors investigate the correlation between the fracture toughness of different AHSS and their crash failure behaviour. Fracture toughness is measured in the frame of fracture mechanics, through the essential work of fracture methodology. Two fracture resistance parameters are characterized: the fracture toughness at cracking initiation, we i, and the essential work of fracture, we . Toughness values are compared with the results of axial impact tests, which are evaluated according to the energy absorbed and the cracking behaviour observed in crash boxes. Results show that fracture toughness permits to describe different crash events in terms of crack initiation and crack propagation and allows ranking AHSS impact resistance; steels with higher we present better crash performance. Therefore, fracture toughness is proposed as a key material property to predict the crash resistance of AHSS and as a relevant design parameter for crash resistant parts.